2020
DOI: 10.3390/jcm9051526
|View full text |Cite
|
Sign up to set email alerts
|

No Differences in Gastrointestinal Bleeding Risk among Clopidogrel-, Ticagrelor-, or Prasugrel-Based Dual Antiplatelet Therapy

Abstract: The risk for gastrointestinal bleeding from dual antiplatelet therapy (DAPT) with new antiplatelets (prasugrel/ticagrelor) compared to clopidogrel is unclear. Aim: To determine the risk and type of major (gastrointestinal bleeding requiring hospitalization) and minor (anemia and iron deficiency) gastrointestinal events with different types of DAPT. Methods: Retrospective observational cohort study of patients who started DAPT after percutaneous coronary intervention. Follow-up was censored after 12 months of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Antiplatelet agents, especially the P2Y 12 antagonist clopidogrel, help patients with evidence of atherothrombotic diseases [ 3 , 4 ]; nevertheless, outcomes remain poor. The causes underlying this phenomenon may be adverse effects such as gastrointestinal disorders and internal bleeding [ 5 ]. Several studies showed that about 30% of patients with atherothrombotic diseases were low responders/nonresponders to clopidogrel, leading to higher ischemic risk [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antiplatelet agents, especially the P2Y 12 antagonist clopidogrel, help patients with evidence of atherothrombotic diseases [ 3 , 4 ]; nevertheless, outcomes remain poor. The causes underlying this phenomenon may be adverse effects such as gastrointestinal disorders and internal bleeding [ 5 ]. Several studies showed that about 30% of patients with atherothrombotic diseases were low responders/nonresponders to clopidogrel, leading to higher ischemic risk [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%